Effectiveness and safety of bortezomib-dexamethasone regimen in patients with multiple myeloma: A prospective observational study - Nijisha N; Sanitha Kuriachan; Mahesh Kumar D; Jumi Jacob (Asian Journal of Medical Sciences, 2024)
Background: Bortezomib and dexamethasone (BD) regimen offers a promising therapeutic approach in multiple myeloma (MM) by inhibiting the proteolytic pathway of tumor cells. Aims and Objectives: This study aims to assess the safety profile and treatment outcomes of MM patients undergoing the BD regimen. Materials and Methods: This prospective observational study included MM patients who received BD regimen. Patients received bortezomib (1.3 mg/m2 intravenous) weekly for 4 weeks along with dexamethasone (40 mg orally) weekly for 4 weeks. Clinical assessments were performed after each cycle, and adverse drug reactions were graded according to National Cancer Institute criteria. Treatment outcomes were evaluated after the 4th cycle based on specific parameters. Results: Thirty-seven patients, with a mean age of 56.2 years, predominantly male (56.8%), were included. Common symptoms included bone pain, fatigue, weight loss, and appetite loss. Toxicities were mainly grade 1 and 2, with peripheral neuropathy (PN) being the most prevalent. The BD regimen exhibited a response rate of 65%, accompanied by significant improvements in bone marrow plasma cells, β2 microglobulin, immunoglobulin assay, and erythrocyte sedimentation rate. In addition, treatment improved performance status, in 51.4% of patients achieving scores above 90 on the Karnofsky scale. Conclusion: The BD regimen demonstrated notable efficacy and tolerability in MM treatment. However, it is associated with a higher risk of PN.